Implementation and evaluation of a multidisciplinary project based on an iterative process of investigative product design - Torres de León, Gloria Azucena; Montoya Reyes, Eduardo; Trejo Alba, Carolina; Camacho Ixta, Ixchel Astrid; Fierro Silva, Salvador (Acta Universitaria, 2019)
This paper is about a case study whose goal is to describe the implementation and evaluation of a multidisciplinary project used as a teaching-learning strategy in the first year of Architecture and Design at the School of Engineering Sciences and Technology of the University of Baja California (ECITEC-UABC, from its Spanish initials). Teachers with different discipline backgrounds related with design participate in this project throughout the semester as co-responsible guides in the development of a design product. Ethnographic methods and field research are applied to establish specific design guidelines in a real applied case. The methodology is the Process of Design Research, merging the work of four Learning Units. The results show that students and teachers accept the enforcement of a project methodology and that, in an early development phase, the students identify the similar approach the different disciplines have in the professional practice, which stimulates the creative process.